The almond Museo Vivente 'F. Monastra': From genetic resources rescue to germplasm collection - Barbera G.; Monte M.; Sottile F. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
During the 1st ISHS Almond Congress, held in 1993 in Agrigento together with the IX Grempa Meeting, the idea to organize an 'on-farm' collection on almond biodiversity in Sicily came up discussing with Francesco Monastra, who was a founding member of the Grempa Group, an unforgettable researcher and friend. The Sicilian almond production and acreage evidenced, a lot before that time, a rapid decrease making the risk of genetic erosion of the old and historical cultivars extremely feasible. In 1997, with the financial support of the Sicilian Government and of the Regional Province of Agrigento, a 5 hectare field collection was realized planting around 300 cultivars recovered from the most traditional almond growing areas throughout the Sicilian territory. The collection was called Museo Vivente del Mandorlo (almond living-museum) and in 1999 it was entitled Francesco Monastra. It is located in the Temple Valley Park, in Agrigento, just at the foot of the Juno Temple.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)